Pengaruh Kepemimpinan, Pelatihan Dan Motivasi Kerja Terhadap Kinerja Aparatur Sipil Negara (ASN) Badan Keuangan Kabupaten Lima Puluh Kota - Sabri; Susandra, Soni; nasfi, nasfi (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2021)
This study aims to analyze the influence of leadership, job training and work motivation on the performance of the State Civil Apparatus (ASN) at the District Finance Agency of Fifty Cities. The type of research that the author uses is quantitative with a descriptive approach. The total population of 65 people and at the same time became the sample in this study using the saturated sample method, meaning that the entire population was the sample. Data were collected through the distribution of questionnaires with a Likert scale model and then tested for the validity and reliability of the questionnaire. The data analysis technique used is the Multiple Linear Regression method using the SPSS 23.00 program. The results of this study are a). Leadership (X1), Job Training (X2) and Work Motivation (X3) have a positive and significant influence on the performance of the State Civil Apparatus (ASN) of the Fifty Cities District Finance Agency, either partially or simultaneously.